Oxygen pressure effect on optical properties and dye degradation of ZnO nanostructured films prepared by sputtering. (5th September 2017) - Reddy, I Neelakanta; Saravanan, K Gobi; Venkata Reddy, Ch; Cho, Migyung; Shim, Jaesool; Kim, Dongseob
Abstract: The effect of oxygen pressure on structural, morphological and photocatalytic properties of ZnO nanostructured films deposited on glass substrates via RF magnetron sputtering was investigated. The structural, morphology and oxidation states of the films were investigated by x-ray diffraction, scanning electron microscopy, atomic force microscopy, and x-ray photoelectron spectroscopy. UV–vis spectroscopy and photoluminescence spectroscopy were used to analyze the degradation and optical properties of ZnO thin films. The grown films showed wurtzite hexagonal crystalline nanostructures with a favored orientation along the direction of (0 0 2) lattice plane. The morphology images showed a hierarchical ZnO nanostructured films with various shapes from circulars to foils and even much more multifaceted circular shapes and triangular sheets-like shapes by varying the oxygen pressure. The foil type ZnO nanostructured films showed significant photocatalytic activity concerning the degradation of methyl orange, mainly due to their surface-to-volume ratio.